Radiopharmaceutical extravasations: a twenty year mini-review - Osborne, Dustin R. (Frontiers in Nuclear Medicine, 2023)
Interest and research into radiopharmaceutical extravasation concepts has risen with the increase in use of radiopharmaceutical therapies, growing access to novel molecular imaging agents, and recent regulatory controversies. This mini-review will examine the literature of the last twenty years to summarize the history of radiopharmaceutical extravasations, determine key trends in imaging and therapies, and highlight critical gaps in research that currently exist. The intent of this work is to provide a summary of this complex topic that helps build awareness and promotes new innovations in this interesting aspect of theranostic radiopharmaceuticals.